Body mass index and hepatic lipase gene (LIPC) polymorphism jointly influence postheparin plasma hepatic lipase activity - Liangcai Nie; Jinping Wang; Luther T. Clark; Aylmer Tang; Gloria L. Vega; Scott M. Grundy; Jonathan C. Cohen (Journal of Lipid Research, 1998)
The -514 polymorphism in the hepatic lipase gene (LIPC) is associated with decreased hepatic lipase activity. In the present study, the interaction between body mass index (BMI), the -514 polymorphism, and hepatic lipase activity was examined in 118 white men and in 51 African American men. BMI was significantly positively correlated with hepatic lipase activity in both populations. BMI was similar in men with genetic differences in hepatic lipase activity, indicating that high hepatic lipase activity did not cause increased BMI. The data therefore suggest that high BMI leads to increased hepatic lipase activity. The actions of BMI and the -514 polymorphism on hepatic lipase activity appear to be additive and independent, rather than synergistic. This finding indicates that hepatic lipase activity is a multifactorial trait, determined in part by polymorphism within the LIPC gene as well as by factors that influence BMI.—Nie, L., J. Wang, L. T. Clark, A. Tang, G. L. Vega, S. M. Grundy, and J. C. Cohen. Body mass index and hepatic lipase gene (LIPC) polymorphism jointly influence postheparin plasma hepatic lipase activity. J. Lipid Res. 1998. 39: 1127–1130.